The level of knowledge about first aid rules among high school students - Jakub Linek; Marta Dudzińska; Agnieszka Zwolak; Joanna Świrska; Agata Smoleń; Robert Łuczyk (Kazimierz Wielki University, 2018)
First aid is defined as a group of activities directed at a person in a sudden health or life threatening state which is performed by somebody who is present at the site of the incident. First aid skills are taught in high school during the Education for Safety and it is an extension of the subject introduced in junior high school. The aim of the study is to evaluate the level of knowledge of high school students on first aid rules. Material and methods: The studying group consisted of 304 students of I, II and III High School in Zamość (F-60,2%, n=183, M-39,8%, n=121). The survey used self-reported proprietary questionnaire. Results: 94,4% (n=287) of the respondents knew correct chest compression to breathing ratio in cardio-pulmonary resuscitation (CPR). This answer was given significantly more commonly by the students from rural areas than the teenagers living in town (97,2%, n=174 vs 90,4%, n=113 respectively, p=0,01). Respondents living in rural areas also more often were able to describe correct procedure both in case of foreign body embedded in the wound (92,1%, n=163 vs 81,6%, n=102, p=0,01) as well as how to dress the wound (73,7%, n=132 vs 60,8%, n=76, p=0,01). Less than a half of studying group knew appropriate management in case of collapse (29,9%) and in case of first grade burn (49,3%). 46,7% of the respondents knew how to differentiate venous from arterial hemorrhage, and in that area male students were giving the correct answer more often than women (58,7%, n=71 vs 39,2%, n=71 respectively, p